Photocatalytic Degradation of Methylene Blue by Fe/ZnO/SiO2 Nanoparticles under Visiblelight - R. M. Mohamed; I. A. Mkhalid; E. S. Baeissa; M. A. Al-Rayyani (Journal of Nanotechnology)
The photocatalytic activity of Fe/ZnO/SiO2 catalysts under visible-light irradiation for the degradation of methylene blue was evaluated. The effect of pH, illumination time, amount of catalyst loaded, and initial dye concentration on the degradation efficiency of methylene blue was investigated. The results reveal that the optimum photocatalytic oxidation conditions of methylene blue are as follows: pH=4 and illumination time is 30 min, the amount of catalyst loading is 0.075 g/L and 50 ppm methylene blue dye concentration. Under these conditions, the removal efficiency of methylene blue was 100%.